2004
DOI: 10.5980/jpnjurol1989.95.817
|View full text |Cite
|
Sign up to set email alerts
|

Carcinomatous Meningitis From Urothelial Carcinoma of Bladder and Ureter: Case Report

Abstract: Carcinomatous meningitis from urothelial carcinoma of the bladder and ureter is rare. A 77-year-old man with invasive bladder cancer and right ureter cancer had been treated with 3 courses M-VAC (methotrexate, vinblastine, epirubicin, cisplatin) chemotherapy. After chemotherapy we performed radical cystectomy and right nephroureterectomy (ileal-neobladder) (TCC, G3, pT3, N0, M0). Sixteen months after operation, patient complained of anorexia, muscular weakness, stiff neck. CT of chest and abdomen, and bone sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The literature includes 22 cases of MC secondary to bladder cancer (Table 1) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . Four of these 22 cases presented with MC and the bladder primary was later diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…The literature includes 22 cases of MC secondary to bladder cancer (Table 1) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . Four of these 22 cases presented with MC and the bladder primary was later diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bishop et al [7] reported 2 patients developing disease after systemic treatment with MTX, vinblastine, Adriamycin, and cisplatin (MVAC). Matsushita et al [8] reported a case occurring 16 months after their patient had had a complete response following chemotherapy and surgery, and Boukriche et al [9] reported a case occurring 4 years after adjuvant treatment for resected bladder cancer. Still, just as many cases present concurrently with widespread systemic disease, suggesting that TCC may have an affinity for the CNS and that carcinomatous meningitis may be more common than realized.…”
Section: Discussionmentioning
confidence: 99%
“…Carcinomatous meningitis is rare in bladder cancer [14]-[16]. Trastuzumab does not cross the blood–brain barrier [17], suggesting that targeting Her2/ neu positive systemic disease may alter the natural history of bladder carcinoma metastasis predisposing to the onset and progression of central nervous system (CNS) disease.…”
Section: Discussionmentioning
confidence: 99%